Causes, consequences, and the future of forest mortality due to climate change - Nate McDowell; Tom Levanič (Acta Silvae et Ligni, 2014)
Mortality of forest trees is growing at an accelerating rate due in part to increasing severity and frequency of droughts. The consequences of increasing forest mortality range from impacts on timber and tourism revenue, reductions in fuelwood availability and carbon storage, and feedbacks that accelerate climate changes. Unfortunately, our understanding of where, when, and how forests die is extremely limited, precluding us from forecasting future changes in forest composition and services. Here we review the state of current knowledge regarding mortality processes, and highlight the urgent scientific challenges that must be overcome if we are to adequately plan for future changes in forest survival and mortality. We suggest that forest monitoring through inventory networks and newly emerging remote sensing techniques should be a high priority for maintenance and development, because only through these observations can we determine what regions and species are most vulnerable to climate change. These datasets are also critical for evaluation of regional to global models of forest dynamics. Without accurate models, forecasts of future forest composition cannot be considered reliable. Furthermore, experimental tests of how the dominant global forest species die are needed to enable models to simulate mortality correctly. Lastly, experimental tests of forest management strategies that can alleviate stress under the novel climate regimes the globe is now experiencing are essential to allow planning for mitigation options in the forestry sector. Increasing forest mortality is now inevitable given the global energy portfolio; however, the ability of science and forestry to quantify, understand, predict, and mitigate impacts on forests remains a viable option to allow planning for future forest management to minimize impacts on the Earth’s forests.